2020
DOI: 10.1098/rsos.200092
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy of Micronesian monitors (Reptilia: Squamata: Varanus ): endemic status of new species argues for caution in pursuing eradication plans

Abstract: In the light of recent phylogenetic studies, we re-assess the taxonomy and biogeography of the Varanus populations distributed in the Micronesian islands of Palau, the Western Carolines and the Marianas. Whether these populations are of natural origin or human introductions has long been contentious, but no study has fully resolved that question. Here, we present molecular and morphological evidence that monitor lizards of the Varanus indicus Group reached both P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 514 publications
(5 citation statements)
references
References 39 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Prior to the introduction of invasive vertebrate predators, nocturnal predation events were likely uncommon on Guam. Therefore, diurnal nest defense should have been a beneficial behavior for reducing predation of Såli eggs and nestlings by Guam's native predators, such as Hilitai and Åga (Dryden, 1965; Faegre et al, 2020; Weijola et al, 2020). The introduction of novel nocturnal predators that hunt when adult Såli are roosting and less able to defend offspring is a selective pressure that effectively circumvents diurnal defense mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the introduction of invasive vertebrate predators, nocturnal predation events were likely uncommon on Guam. Therefore, diurnal nest defense should have been a beneficial behavior for reducing predation of Såli eggs and nestlings by Guam's native predators, such as Hilitai and Åga (Dryden, 1965; Faegre et al, 2020; Weijola et al, 2020). The introduction of novel nocturnal predators that hunt when adult Såli are roosting and less able to defend offspring is a selective pressure that effectively circumvents diurnal defense mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Current major predators of birds on the island include non‐native brown treesnakes and feral cats. Historically, native predators have included Hilitai (monitor lizards, Varanus tsukamotoi ) and Åga (Mariana crows, Corvus kubaryi ) (Dryden, 1965; Faegre et al, 2020; Weijola et al, 2020), both of which are exclusively diurnal.…”
Section: Methodsmentioning
confidence: 99%
“…These and other Micronesian populations have long been included under the name Varanus indicus and reported to have been introduced during the Japanese administration. However, recent molecular and morphometric studies revealed that monitor lizards from western Micronesia form a distinct clade (and two separate species) and appear to have colonized those islands by natural dispersal several hundred thousand years ago rather than by more recent human-mitigated introduction (Weijola et al 2019(Weijola et al , 2020. Weijola et al (2020) Early reports of monitors and descriptions of lizards probably referring to monitors in the FSM predate the Japanese administration and suggest a longer history of Varanus in this region than is generally thought: de la Corte (1875) mentioned "iguanas" on Pohnpei, Cabeza Pereiro (1895) identified a large lizard that he saw on Pohnpei during the 1890s as a monitor, and Lesson (1839 as translated by Ritter and Ritter 1982:48) reported seeing a gecko and two other kinds of lizards on Kosrae during 5-15 June 1824, a greencolored species [probably Lamprolepis smaragdina] and one with a blue tail and golden stripes on its back [almost certainly Emoia sp.…”
Section: Monitor Lizards In Micronesiamentioning
confidence: 99%
“…Genetic tools have effectively unravelled cryptic lineages, identified new species of monitor lizards and helped in unfolding complex phylogenetic relationships (Smith et al, 2007;Smissen et al, 2013;Maryan et al, 2014;Dowell et al, 2016). Molecular studies with multilocus approaches have revealed immense amounts of information helping in the separation of divergent assemblages of monitor lizard species across African (Portik and Papenfuss, 2012), Indonesian (Welton et al, 2010a;Weijola et al, 2016Weijola et al, , 2017Weijola et al, , 2019Weijola et al, , 2020, Australian (Smissen et al, 2013) and Asian (Vidal et al, 2012) geographies. In this study, we investigated the genetic structure and evolutionary relationship of V. bengalensis with other monitor lizard species, focusing on the Himalayan foothills, a biodiversity hotspot, to provide insight into how landscape structure, and geological and climatic processes have shaped species differentiation.…”
Section: Introductionmentioning
confidence: 99%